Hydrogen bonding and π–π interactions in the cocrystal salt [Fe(bpe)2(H2O)4](TCEP)2·2(bpe) [bpe is trans‐1, 2‐bis(pyridin‐4‐yl)ethene and TCEP is 1, 1, 3, 3‐tetracyano‐2‐ethoxypropenide]. Issue 3 (21st February 2019) - Addala, Abderrezak; Geiger, David K.; Setifi, Zouaoui; Setifi, Fatima
Abstract : The solid‐state structure of the cocrystal salt tetraaquabis[ trans ‐1, 2‐bis(pyridin‐4‐yl)ethene]iron(II) bis(1, 1, 3, 3‐tetracyano‐2‐ethoxypropenide)– trans ‐1, 2‐bis(pyridin‐4‐yl)ethene (1/2) is reported. Density functional theory is used to explore the strengths of the observed O—H…N hydrogen bonding and π–π intermolecular interactions. Abstract : The cocrystal salt tetraaquabis[ trans ‐1, 2‐bis(pyridin‐4‐yl)ethene‐κ N ]iron(II) bis(1, 1, 3, 3‐tetracyano‐2‐ethoxypropenide)– trans ‐1, 2‐bis(pyridin‐4‐yl)ethene (1/2), [Fe(C12 H10 N2 )2 (H2 O)4 ](C9 H5 N4 O)2 ·2C12 H10 N2, is a rare example of a mononuclear Fe II compound with trans ‐1, 2‐bis(pyridin‐4‐yl)ethane (bpe) ligands. The complex cation resides on a crystallographically imposed inversion center and exhibits a tetragonally distorted octahedral coordination geometry. Both the symmetry‐independent bpe ligand and the cocrystallized bpe molecule are essentially planar. The 1, 1, 3, 3‐tetracyano‐2‐ethoxypropenide counter‐ion is nonplanar and the bond lengths are consistant with significant electron delocalization. The extended structure exhibits an extensive O—H…N hydrogen‐bonding network with layers of complex cations joined by the cocrystallized bpe. Both the coordinated and the cocrystallized bpe are involved in π–π interactions. Hirshfeld and fingerprint plots reveal the important intermolecular interactions. Density functional theory was used to estimate the strengths of the hydrogen‐bonding and π–π interactions, and suggest that the O—H…N hydrogen bonds enhance the strength of the π‐interactions by increasing the polarization of the pyridine rings.